Exploring self-directed AI literacy through discourse analysis of learning platform webinars - The, Hery Yanto (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2025)
Educators have critical roles in keeping up with the growing influence of Artificial Intelligence (AI) in the fast-changing world of language education and literary research. One promising approach to connect AI advancements with teaching practices is through self-directed learning facilitated by personal learning networks. However, despite the increasing number of resources like “AI for Educators”, many teacher-educators are either unaware of or lack the motivation to take advantage of these opportunities. This study examines how self-learning initiatives can empower educators to enhance their AI literacy. It uses Paul Gee’s discourse analysis framework to analyze three recorded webinars from the AI for Educators platform. The analysis focuses on how language and meaning are constructed within these digital learning environments to shape an understanding of AI’s roles and values in education. The results indicate that these webinars not only provide accessible entry points for grasping the technical and ethical aspects of AI but also act as a springboard for educators to view AI as a tool for enhancement rather than a threat. The understanding of AI as a new literacy practice is deepened, highlighting its potential to support education in general and specifically foreign language acquisition. This study proposes that encouraging self-directed AI learning through thoughtfully designed, discourse-rich platforms could serve as an effective model for professional development, particularly in disciplines such as literary studies, where critical inquiry, interpretation, and ethical considerations are essential.